Capex and opex expenditures - Ganat, T.A.-A.O. (Springer, 2020)
This chapter is discussing the expenditures associated to all investment (CAPEX) that is made in advance, and the operational expenses (OPEX) that will occur from the first day startup the production until the abandonment day. Roughly numbers will be presented for these expenses in deepwater projects and will see what is the key assumptions must be considered when keying these values to any project. Accessible records that cover these values will be revealed together with the approximation costs and methodology. Â© The Author(s), under exclusive license to Springer Nature Switzerland AG 2020.